IDENTIFIKASI SIGNIFICANT VALUE PADA LANSKAP BUDAYA SUKU MATABESI SEBAGAI UPAYA PENGEMBANGAN PARIWISATA DAN EKONOMI KREATIF KABUPATEN BELU - Nuraini Nuraini; Irawan Setyabudi (Universitas Tribhuwana Tunggadewi, 2019)
The Matabesi tribe is the oldest tribe in Belu Regency. The Matabesi Tribe community lives and develops into a traditional village. Matabesi society still use nature and the environment to fulfill their daily lives. The Matabesi Tribe area has a lot of tourism potential that bus is developed into a cultural tourism area. The purpose of this study was to identify the Significant Value possessed by the Matabesi Tribe. This research uses descriptive method, observation and indepth interview with key person to determine the significant value. Research result the cultural landscape area of Matabesi Tribe has 5 significant values namely history, science, culture, religion and education. Based on Tourism Law No. 10 of 2009 concerning tourist destinations, the Matabesi Tribe can be developed which can support the creative economy of the Matabesi Tribe through the development of facilities, developing tourist attraction and developing accessibility derived from the local wisdom of the Matabesi Tribe.